The Potential and Pitfalls of Artificial Intelligence in Nursing: Preserving Humanity in the Face of Technological Advancement - Göktaş, Polat; Küçükkaya, Aycan; Karaçay, Pelin (Florence nightingale journal of nursing, 2024)
Cite this article as: Göktaş, P., Küçükkaya, A., & Karaçay, P. (2024). The potential and pitfalls of artificial intelligence in nursing: preserving humanity in the face of technological advancement. Florence Nightingale Journal of Nursing, 32(1), 116-117.